2012
DOI: 10.2486/indhealth.ms1313
|View full text |Cite
|
Sign up to set email alerts
|

Work Experience, Work Environment, and Blood Exposure among Home Care and Hospice Nurses

Abstract: Blood exposure rates among home care and hospice nurses (RNs) in the United States are markedly lower for nurses with more home care/hospice experience, whether or not they have more total years of nursing experience (i.e., in other work environments). This study examined whether the protective effect of home care/hospice experience was greater for nurses who worked under three types of circumstances that are typical of the home care/hospice work environment and conducive to blood exposure. A mail survey was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This study found that the association holds for nurses who did and did not use a safetyengineered medical device the last time they used that particular type of device, do and do not always use the selected item of PPE when it is indicated, had fewer or greater years of experience in home care/hospice, worked full time, did and did not have to rush during home visits, and seldom or often visited homes with adverse conditions. The findings for these subgroups are important because these factors are prevalent in home care/hospice [18] and several have been associated with blood exposure [11,12]. If the association between safety climate and blood exposure proves to be causal, these findings will indicate that, while improving the above factors is important for reducing nurses' blood exposure [11], such improvement will need to be accompanied by a strong safety climate in order to further reduce their exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the association holds for nurses who did and did not use a safetyengineered medical device the last time they used that particular type of device, do and do not always use the selected item of PPE when it is indicated, had fewer or greater years of experience in home care/hospice, worked full time, did and did not have to rush during home visits, and seldom or often visited homes with adverse conditions. The findings for these subgroups are important because these factors are prevalent in home care/hospice [18] and several have been associated with blood exposure [11,12]. If the association between safety climate and blood exposure proves to be causal, these findings will indicate that, while improving the above factors is important for reducing nurses' blood exposure [11], such improvement will need to be accompanied by a strong safety climate in order to further reduce their exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the objective of the present study was to examine the association between safety climate and blood exposure in a population of home care and hospice nurses. This study builds on previous work by examining safety climate and blood exposure in the context of other factors that have been found to be associated with reduced exposure, including use of PPE and safety devices, work experience, type of employment, and characteristics of the work environment [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…clutter and obstacles). The permanent physical environment issues included cramped conditions (strong evidence: Hale & Piggot, 2005;moderate evidence: Craven et al, 2012;Kalman & Andersson, 2014;Markkanen et al, 2007;Munck et al, 2011;Quinn et al, 2009;Skoglind-Ohman & Kjellberg, 2011;Swedberg et al, 2013), poor lighting (moderate evidence : Beer et al, 2014;Leiss, 2012;Munck et al, 2011), poor access to stairs (moderate evidence: Kim et al, 2010) and unsafe flooring (limited evidence: Conneeley, 1998). There are also less permanent risk factors associated with clutter and obstacles (moderate evidence : Beer et al, 2014;Leiss, 2012;Markkanen et al, 2007;Quinn et al, 2009;Skoglind-Ohman & Kjellberg, 2011) and awkward working positions for clinical, IT and writing tasks (strong evidence: Cheung et al, 2006;Dellve et al, 2003;Ono et al, 1995;Brulin et al, 2001; moderate evidence: Kim et al, 2010;Munck et al, 2011;Pohjonen et al, 1998;Quinn et al, 2009;Simon et al, 2008).…”
Section: Environments (Health Policy Community Physical and Social)mentioning
confidence: 99%
“…The social environment issues range from additional tasks to distractions from pets, children and televisions (strong evidence: Cheung et al, 2006;Hale & Piggot, 2005; moderate evidence: Leiss, 2012;Sims-Gould et al, 2013;limited evidence: Denton et al, 2002) through to issues of cleanliness and insect and rodent infestations (moderate evidence: Sims-Gould et al, 2013;Quinn et al, 2009;limited evidence: Denton et al, 2002). The close interaction can lead to additional requests from patients which were not on the treatment plan and/or outside the caregiver job description (moderate evidence : Beer et al, 2014;Skoglind-Ohman & Kjellberg, 2011;Swedberg et al, 2013;limited evidence: Denton et al, 2002).…”
Section: Environments (Health Policy Community Physical and Social)mentioning
confidence: 99%
See 1 more Smart Citation